Circular economy implementation and business performance: The mediating role of environmental performance in the Chinese energy production enterprises - Dong, Hao; Wang, Bo; Li, Jiaze; Li, Zongwu; Li, Fujing; Wang, Chuangjia (Frontiers in Environmental Science, 2022)
Sorting out the implementation mechanism of circular economy and verifying its impact on enterprise performance is of great practical significance for the comprehensive promotion and in-depth implementation of circular economy in Chinese enterprises. By collecting the micro data of 295 Chinese energy production enterprises, the partial least square structural equation (PLS-SEM) method is used to empirically analyze the impact of circular economy implementation mechanism on enterprise performance. The results show that the implementation mechanism of circular economy includes three dimensions: reduce, reuse and recycle. The implementation of circular economy can effectively promote the joint improvement of enterprise environmental protection performance and business performance; At the same time, the environmental performance of enterprises has a significant positive impact on their business performance.